Intestinal Hyperpermeability in Gulf War Veterans with Chronic Gastrointestinal Symptoms - Zhang, Buyi (J Clin Gastroenterol, 2019)
BACKGROUND: Well over 700,000 United States military personnel participated in the Persian Gulf War in which they developed chronic health disorders of undetermined etiology. Up to 25% of Veterans had persistent and chronic GI symptoms, which they suspected were related to their military service in the Gulf. AIM: The overall aim of the current study was to evaluate intestinal permeability in previously deployed Gulf War Veterans who developed chronic GI symptoms during their tour in the Persian Gulf. Methods: To accomplish this, we evaluated intestinal permeability (IP) using the urinary lactulose/mannitol test. Measurements of intestinal permeability were then correlated with mean ratings of daily abdominal pain, frequency of bowel movements, and consistency of bowel movements on the Bristol Stool Scale in all Veterans. RESULTS: A total of 73 veterans had documented chronic GI symptoms (diarrhea, abdominal pain) and were included in the study. A total of 29/73 (39%) of veterans has increased IP and had a higher average daily stool frequency (p<0.05); increased liquid stools as indicated by a higher Bristol Stool Scale (p<0.01); and a higher mean M-VAS abdominal pain rating (p<0.01). Pearson correlation coefficients revealed that there was a positive correlation between increased IP and stool frequency, Bristol Stool Scale, and M-VAS abdominal pain rating. CONCLUSION: Our study demonstrates that deployed Gulf War Veterans with persistent GI symptoms commonly have increased intestinal permeability that potentiates the severity of abdominal pain, diarrhea, and stool consistency. These new findings in our study are important as they may lead to novel diagnostic biomarkers for returning Gulf War Veterans who suffer from chronic functional gastrointestinal disorders. These advances are also important for an increasing number of veterans who are now serving in the Persian Gulf and are at a high risk of developing these chronic pain disorders.